2014
DOI: 10.1155/2014/694948
|View full text |Cite
|
Sign up to set email alerts
|

CD226rs763361 Is Associated with the Susceptibility to Type 1 Diabetes and Greater Frequency of GAD65 Autoantibody in a Brazilian Cohort

Abstract: CD226 rs763361 variant increases susceptibility to type 1 diabetes (T1D) in Caucasians. There is no data about CD226 variants in the very heterogeneous Brazilian population bearing a wide degree of admixture. We investigated its association with T1D susceptibility, clinical phenotypes, and autoimmune manifestations (islet and extrapancreatic autoantibodies). Casuistry. 532 T1D patients and 594 controls in a case-control study. Initially, CD226 coding regions and boundaries were sequenced in a subset of 106 T1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
3
16
0
1
Order By: Relevance
“…In our analysis, the minor T allele appeared to be aggressive, with 28.3% of children with T1D carrying the TT genotype compared with 11.2% of the healthy controls. These findings confirm previously published data from Brazilian cohorts published by Mattana et al (2014), which showed that the presence of the T allele might be one of the genetic risk factors for T1D.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our analysis, the minor T allele appeared to be aggressive, with 28.3% of children with T1D carrying the TT genotype compared with 11.2% of the healthy controls. These findings confirm previously published data from Brazilian cohorts published by Mattana et al (2014), which showed that the presence of the T allele might be one of the genetic risk factors for T1D.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, the rs763361 SNP in the CD226 gene has been reported to be associated with susceptibility to autoimmune diseases Douroudis et al, 2010;Maiti et al, 2010), including T1D in a Brazilian population (Mattana et al, 2014). Moreover, Lofgren et al (2010) identified the potential interference of the rs727088 SNP on the regulation of CD226 transcription both in T cells and natural killer cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A single nucleotide polymorphism in CD226 can result in the amino acid substitution Gly 307 Ser (rs763361). This correlates with the development of a wide range of immune‐related diseases, such as systemic lupus erythematosus, systemic sclerosis (SSc), type I diabetes and rheumatoid arthritis (RA) …”
Section: Dnam‐1 In Immune‐related Diseasesmentioning
confidence: 99%